ANALISA PENGARUH PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN LQ 45 DI BURSA EFEK INDONESIA - Lumowa, David (Universitas Sam Ratulangi, 2015)
This research aims to test the effects of profitability on share prices of companies listed in the LQ 45 index in the Indonesian Stock Exchange.Â Profitability is measured using the return on equity (ROE) and earnings per share (EPS) ratios. Using purposive sampling on companies listed in the LQ 45 index in 2011- 2014 yielded data samples from 11 companies.Â Running a simple linear regression and and a multiple regression on the variables results in showing that simultaniuosly ROE, EPS does significantly effects share prices. When tested partially ROE and EPS also proves to have significant effects on Share Price.